The use of cobs, a by-product of maize grain, for energy production in anaerobic digestion - Blandino, Massimo; Fabbri, Claudio; Soldano, Mariangela; Ferrero, Carlo; Reyneri, Amedeo (Italian Journal of Agronomy, 2016)
Owing to the rising energy demand and the conflict between food, feed and energy crops for agricultural land, there is a growing need for alternative biomasses for energy purposes. New developments in harvesting technology have created the possibility of harvesting cobs as a by-product of maize grain harvesting. The aim of the present work has been to evaluate the potential and limitations of maize cob utilisation in an anaerobic digestion chain, considering the main agronomic, productive and qualitative traits. Maize grain and cob yields as well as the moisture content of samples collected from 1044 (farm) fields (located) in North West Italy have been determined over the 2012 growing season. Moreover, 27 representative fields were harvested using a modified combine-harvester that is able to collect maize grains and threshed cobs separately. The chemical composition and biochemical methane potential (BMP) of the cobs have been analysed. The relative potential yield of maize cobs was established as 18.7% of the grain mass, while the wet cob yield recorded in the field after mechanical harvesting was 1.6 t ha–1. The total solid content was 60%. Fibre fractions represented over 85% of the dry cob matter, lignin content was about 16%, while the protein, ash, lipids and macro-elements (nitrogen, phosphorus, potassium) contents were very low compared to the whole-plant maize used for silage. The average BMP of wet threshed cob was 250±20 Nm3 t VS–1. Collected data have underlined that maize cobs could be used as a sustainable feedstock for anaerobic digestion processes.